If God’s Existence is Unprovable, Then is Everything Permitted? Kant, Radical Agnosticism, and Morality (Diametros, 2014)
This essay is about how four deeply important Kantian ideas can significantly illuminate some essentially intertwined issues in philosophical theology, philosophical logic, the metaphysics of agency, and above all, morality. These deeply important Kantian ideas are: (1) Kant’s argument for the impossibility of the Ontological Argument, (2) Kant’s first “postulate of pure practical reason,” immortality, (3) Kant’s third postulate of pure practical reason, the existence of God, and finally (4) Kant’s second postulate of pure practical reason, freedom.